The Da'wah Movement of Ulama Dayah (Analysis the Da'wah Movement of Têungkū Hasanoel Bashry) - Zulfikar; Saiful Bahri; Muslem; Fatahillah; Amiruddin; Muhibuttibri (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
The purpose of this research is to find out about how the da'wah movement of Têungkū Hasanoel Bashry one of the dayah scholars in conducting da'wah activities, and to find out the basis of the da'wah movement of Têungkū Hasanoel Bashry, where the da'wah movement can be said to be able to answer various problems and problems experienced by the people of Aceh at this time, especially religious issues. This type of research is a qualitative research using a character study that aims to provide answers to how the da'wah movement developed by dayah scholars. The results of this study illustrate how the missionary movement Têungkū Hasanoel Bashry, starting from establishing the Al-Aziziyah Islamic College in 2003, developing dayah economics, forming social organizations such as MUDI alumni ties and TASTAFI administrators, cooperating with the government and several countries, and had initiated the birth of a local political party Aceh Daulat Party (PDA) as a forum for entry into the legislative body for dayah graduates. The foundation of the da'wah movement of Têungkū Hasanoel Bashry is to hold fast to the Al-Qur'an and Hadith and Ijma 'of the previous scholars, so as to be able to answer the various problems faced by the people of Aceh at this time, starting from the problems of the Aqeedah, Sharia, and contemporary problems. The da'wah movement Teungku Hasanoel Hasano Bashry has been able to inspire the public to participate in various da'wah activities which are conveyed through discussion media, questions and answers, print media, electronic media and social media. So the da'wah that he delivered was liked by various groups of people, men and women, parents and also young people.